2021
DOI: 10.3389/fsurg.2021.799442
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Laparoscopy—A Historical Overview

Abstract: The advent of laparoscopy marked a fundamental change in the evolution of medicine. The procedure progressed consistently after the first time it was performed in a human being nearly a hundred years ago. The 1960's and 1980's witnessed groundbreaking changes. During this time, laparoscopy evolved from a purely diagnostic procedure into an independent surgical approach. Outstanding pioneers of the times were Palmer, Frangenheim and Semm. Laparoscopy advanced rapidly and influenced gynecology as well. The proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 33 publications
0
36
0
1
Order By: Relevance
“…Our study demonstrated new findings compared with the meta-analysis by Cirocchi et al 14 We showed lower 30-day mortality, overall morbidity, LOS, EBL, and postoperative pain, with similar postoperative leakage and need for reoperation in LOPR compared with OOPR. Compared with open surgery, laparoscopic surgery offers reduced pain, use of analgesia, wound infection, length of operation, EBL, and LOS 59–61 . However, literature is still equivocal in the context of PPU.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study demonstrated new findings compared with the meta-analysis by Cirocchi et al 14 We showed lower 30-day mortality, overall morbidity, LOS, EBL, and postoperative pain, with similar postoperative leakage and need for reoperation in LOPR compared with OOPR. Compared with open surgery, laparoscopic surgery offers reduced pain, use of analgesia, wound infection, length of operation, EBL, and LOS 59–61 . However, literature is still equivocal in the context of PPU.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with open surgery, laparoscopic surgery offers reduced pain, use of analgesia, wound infection, length of operation, EBL, and LOS. [59][60][61] However, literature is still equivocal in the context of PPU. While Cirocchi stable compared with OOPR as carbon dioxide insufflation during laparoscopy results in increased intra-abdominal pressure with resultant reduction in stroke volume and cardiac output.…”
Section: Discussionmentioning
confidence: 99%
“…US Food and Drug Administration approved the ORC as the first anti-adhesion product, which showed a good effect in animal models, besides an extreme biocompatibility [57][58][59]. In vivo, in gynecological and general surgery, in laparoscopy and in laparotomy, ORC was proven a reduction in the formation of adhesions [60].…”
Section: Adhesion Barriermentioning
confidence: 99%
“…Due to the rapid development of minimally invasive technology over the past several decades, laparoscopic surgery has gradually matured, and many new and advanced laparoscopic instruments and facilities have been developed and employed [ 1 , 2 ]. Laparoscopic surgery, as one of the most prominent minimally invasive surgical techniques in the 21st century, has been successfully applied in a wide range of surgical fields, including general surgery, thoracic surgery, urology, and gynecology, which has become a major direction in the development of surgery [ 3 , 4 ]. However, laparoscopic surgery is often more challenging than traditional open surgery due to the limited degree of freedom of laparoscopic instruments, their low flexibility, and their limited tactile feedback [ [5] , [6] , [7] ].…”
Section: Introductionmentioning
confidence: 99%